2017
DOI: 10.1111/myc.12664
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 1,3‐β‐D‐glucan for diagnosing invasive fungal diseases in children

Abstract: Plasma 1,3-β-D-glucan (BDG) is indicated as a tool for early diagnosis of invasive fungal diseases (IFD). However, data on its diagnostic value are scarce in children. Therefore, definition of BDG test performance in paediatrics is needed. BDG was evaluated in children admitted to "Istituto Giannina Gaslini," Genoa, Italy, who developed clinical conditions at risk for IFD. Results were analysed for sensitivity, specificity, predictive values, likelihood ratios, accuracy, informedness and probability of missing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, some studies suggested that the cut‐off value used in adults was too low for children 21,22 because many factors in neonates could increase the BDG values. Indeed, the different cut‐off values suggested in neonate infants in previous studies ranged from 106 to 305 pg/mL 11,12,23 . Otherwise, the diagnostic performance may vary depending on the BDG assay kit used such as Fungitell, Dynamiker Fungus or GKT‐5M and the studied population 13,24 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, some studies suggested that the cut‐off value used in adults was too low for children 21,22 because many factors in neonates could increase the BDG values. Indeed, the different cut‐off values suggested in neonate infants in previous studies ranged from 106 to 305 pg/mL 11,12,23 . Otherwise, the diagnostic performance may vary depending on the BDG assay kit used such as Fungitell, Dynamiker Fungus or GKT‐5M and the studied population 13,24 .…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the different cut-off values suggested in neonate infants in previous studies ranged from 106 to 305 pg/mL. 11,12,23 Otherwise, the diagnostic performance may vary depending on the BDG assay kit used such as Fungitell, Dynamiker Fungus or GKT-5M and the studied population. 13,24 Indeed, some studied populations in false-positive BDG results as observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional ‘gold standard’ is microbial culture, but Aspergillus culture requires an extended time period and has a low detection sensitivity. Calitri et al [ 8 ] suggested the G test as a screening tool for early diagnosis of invasive fungal disease in children, but this suggestion has not been widely accepted because of many false-positives including piperacillin treatment, hemodialysis, blood product transfusion, and bacteremia [ 9 ]. In immunosuppressed and critically ill patients, the G test has a sensitivity of 88% and a specificity of 82% for probable IPA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-culture assays have been studied for the early diagnosis of IC in neonates and thus initiation of preemptive therapy with the goal to improve the outcome. (1,3)-β- d -glucan (BDG), a reliable biomarker of most clinically relevant fungi in adults, has been studied very little in neonates with variable results [79,80]. In a more recently published study of premature neonates comparing those with proven or probable invasive yeast infections with controls, BDG was shown to have promising results [81].…”
Section: Management Of Invasive Candidiasis In Neonatesmentioning
confidence: 99%